Smart Ultrasonic Glasses for Blind People using Piezoelectric Sensors (International Journal of Scientific Research in Science and Technology, 2025)
Assistive Technology refers to devices that allow people with disabilities to maintain or increase their basic function capabilities. For people with visual impairment, there has been remarkable development in the field of assistive tech- nology, the emergence of wearable devices paving the way for development of Electronic Travel Aids(ETAs) that are used for obstacle detection and navigation.[2] These travel aids rely upon Camera-based systems and Ultrasonic sensors in order to provide guidance but these components require continuous power that limits their usability. This study aims to explore the addition of Piezoelectric sensors as a power source that is renewable, making the Smart ultrasonic glasses self-sustaining, without requiring frequent charging. A systematic review of existing research work that has contributed to the current technology and recent developments has been conducted[5]. The findings indicate that by utilizing Piezoelectric Nanogenerators (PENGs) and Zigzag- structured PVDF- harvesters, the energy generated by the bodily motions of humans (the energy that generally goes waste or gets released in form of heat to environment) can be converted into an ideal power source. Although, there are several challenges such as energy storage limitation, environmental dependencies, and the most important one Low Power Output that needs to be addressed before real world deployment of any such technology[7]. This study aims to propose a possible and viable solution for development of Energy-efficient glasses for visually impaired individuals.
Keywords: Visually impaired assistive technology; Wearable electronic travel aids (ETAs); Self-powered wearable devices; PVDF-based piezoelectric sensors; Biomechanical energy harvesting; Human motion energy conversion